CORRECTION EQUATION OF RAINFALL DATA MAXIMUM A DAY ON TROPICAL RAINFALL MEASURING MISSION (TRMM) IN SEKAYAM SUB-WATERSHED - Simbolon, Roy Binsar Sahat Maruli Tua; Soeryamassoeka, SB; Umar, Umar (Jurnal Teknik Sipil, 2023)
Flooding can occur because the volume of water flowing in a river exceeds its drainage capacity. The high rainfall intensity can cause the Sekayam River to overflow in Sanggau Regency. A maximum of 1 (one) day of rainfall data from observation stations is needed for flood control and management. However, some observation stations still need complete 1 (one) day maximum rainfall data. One alternative that can be used to obtain rainfall data is to utilize the TRMM satellite. However, the data generated by the TRMM satellite cannot be fully utilized due to interference with infrared and microwave radiation in the atmosphere. It is necessary to make corrections first before rainfall data is used. Correction is done using the correction equation obtained through the test results.    Testing begins with quality testing of observation station rainfall data by conducting homogeneity testing using the data analysis tool with the t-test method: two samples assuming equal variances in MS. Excel and consistency testing using the Worsley Likelihood Ratio Test method. Then, the TRMM satellite rainfall data is filtered by looking at the correlation coefficient results with the condition â‰¥ 0.5 against the observation station data, which has homogeneous and consistent data properties. TRMM rainfall data that passes will go through the calibration and validation stages. The correction equation obtained during the calibration stage and produces the most significant correlation coefficient in the validation stage will be used to correct TRMM satellite rainfall data so that TRMM satellite rainfall data will be obtained after correction. Data after correction will be tested again with data before correction to see the data quality by looking at the results of RMSE and relative bias.The homogeneity and consistency test of observation stations states that all observation stations have homogeneous and consistent results. TRMM rainfall data that passes the data filtering stage is 21 Grids. TRMM rainfall data with a correction equation with the highest correlation coefficient results is on Grid 27 with the correction equation Y = 0.976 x - 10.685 and a correlation coefficient of 0.737. The correction equation is used to correct rainfall data on 21 Grids that have passed the data filtering stage. The results of RMSE and relative bias in TRMM rainfall data after correction using the correction equation Y = 0.976 x - 10.685 show tiny and satisfactory results in interpretation so that the correction equation can be utilized as a correction of TRMM rainfall data in the Sekayam Watershed.